Learning application of Lampung language based on multimedia software - Susilowati, Tri; Shukri Mat The, Kamarul; Mohd. Nasir, Badlihisham; Ghafar Don, Abdul; Huda, Miftachul; Hensafitri, Talia; Maseleno, Andino; ., Oktafianto; Irawan, Dedi (International Journal of Engineering and Technology, 2018)
In the learning method of Lampung language in Junior High School 1 Pugung still using conventional method so that the learning process of Lampung language in Junior High School 1 Pugung become less interactive and less fun so that the students pay less attention to what is delivered by the teacher. Lampung language is one of the regional languages in Indonesia, the language of Lampung itself must be studied when students who are in Lampung province who sit in junior high school. So the author makes a multimedia application using Adobe Flash which is used for learning Lampung language in Junior High School 1 Pugung become more interactive and fun, thus helping students to focus in learning Lampung language.Â